Research advances in drug therapy of endometriosis - Shi, Jianyou; Tan, Xin; Feng, Guimei; Zhuo, Yuan; Jiang, Zhongliang; Banda, Srikanth; Wang, Lin; Zheng, Wei; Chen, Lu; Yu, Dongke; Guo, Chun (Frontiers in Pharmacology, 2023)
Endometriosis is one of the most common benign gynecological disorders in reproductive-aged woman. The major symptoms are chronic pelvic pain and infertility. Despite its profound impact on women’s health and quality of life, its pathogenesis has not been fully elucidate, it cannot be cured and the long-term use of drugs yields severe side effects and hinders fertility. This review aims to present the advances in pathogenesis and the newly reported lead compounds and drugs managing endometriosis. This paper investigated Genetic changes, estrogen dependent inflammation induction, progesterone resistance, imbalance in proliferation and apoptosis, angiogenesis, lymphangiogenesis and neurogenesis, and tissue remodeling in its pathogenesis; and explored the pharmacological mechanisms, constitutive relationships, and application prospects of each compound in the text. Up to date, Resveratrol, Bay1316957 and bardoxifene were effective against lesions and pain in controlled animal studies. In clinical trials, Quinagolide showed no statistical difference with the placebo group; the results of phase II clinical trial of IL-33 antibody have not been announced yet; clinical trial stage III of vilaprisan was suspended due to drug toxicity. Elagolix was approved for the treatment of endometriosis-related pain, clinical studies of Elagolix for the pretreatment of patients with endometriosis prior to IVF treatment has not fulfilled. The results of clinical study of Linzagolix in patients with moderate to severe endometriosis-related pain have not been disclosed yet. Letrozole improved the fertility of patients with mild endometriosis. For endometriosis patients with infertility, oral GnRH antagonists and aromatase inhibitors are promising drugs, especially Elagolix and Letrozole.